Accounting Students' Ethical Perceptions About Love of Money, Machiavellian, Idealism, and Spiritual Intelligence - Ratna Pangesti; Mursalam Salim; Sahrul Ponto (Faculty of Business and Economics , Universitas Yapis Papua, 2023)
A student's ethical perception of information will be determined by the level of understanding, intellectualism, and idealism as well as religious norms attached to the person. This research aims to test and analyze the factors of love of money, Machiavellianism, idealism, and spiritual intelligence on accounting students' ethical perceptions. This type of research is explanatory quantitative research using survey methods. The survey was conducted by taking a sample of 97 respondents using a non-probability sampling ( judgment) design sampling. The collected sample data was analyzed using the structured equation partial least squares (SEM-PLS) analysis method. The results of this research explain that accounting students' ethical perceptions are influenced by Machiavellian, idealism and spiritual intelligence, while the love of money does not affect accounting students' ethical perceptions.